Combatting workplace aggression in detainee transport: the Dutch case. Issue 1 (11th January 2016) - Lasthuizen, Karin; Paanakker, Hester
Abstract : Purpose: – In Dutch detainee care custodial transport police officers experience high levels of aggression and violence from detainees. Being a first of its kind in the Netherlands, the purpose of this paper is to unravel the true nature and origins of such workplace aggression against transport officers and focuses on the role of street-level leadership and leadership by management for its mitigation and prevention. Design/methodology/approach: – Unique in such closed institutions as the prison system, the study employs an extensive mixed methods approach, combining observations, interviews and survey data collected among transport officers and detainees in 2012-2013. Findings: – The research shows that within the exercised street-level leadership of transport officers especially staff orientation towards detainees has great impact. Perceived inappropriate treatment is likely to increase detainees' aggressive behaviours, with potentially detrimental effects such as heightened levels of officers' job stress, decreased safety and decreased quality of detainee transport. The solutions offered indicate that while transport officers could benefit from a supportive staff orientation, transport police management might need to pay more attention to rule enforcement leadership within their efforts to optimize working conditions. Originality/value: – The major practical implication of this research is the potential impact of training in affecting the decisions of frontline public employees in a way that their street-level leadership practices manifest the organizational values and alignment with societal values to ensure an adequate public sector service delivery.